Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Detecting Differential Items Functioning of a Criterion-Referenced Test for a Calculus Course (1) According to the modern theory; for students at Sana’a University according to the variables (gender, system, college) Mrs. Sawsan Hasan Abo-Hadi, Prof. Tawfiq Ali A’alem 2. The reality of inter-studies and the obstacles to activating them in the College of Education at King Saud University from the point of view of postgraduate students at the college Mr. Badr Abdulaziz Saad Al Daoud 3. Educational significances for concept of Wealth and children in the Holy Quran Prof. Safiah Abdullah A. Bakheet , Mrs. Jawaher Abdullah Alzhrani, Mrs. Khlood Ali Alelyani, Mrs. Safa Awad Altalhi, Mrs. Aisha Abdullah Akram Al- Deen 4. The Impact of Using Augmented Reality Patterns (Fixed Pattern, Moving Pattern) on the Academic Achievement for Basic Stage Students in Islamic Education Subject Mrs. Noor Belal Moustafa, Dr. Manal Ata Altawalbeh 5. The Effectiveness of proposed electronic course to develop cognitive awareness of cybersecurity among secondary school students in the city of Jeddah Mrs. Bayan Bakheet Almatrafi, Co-Prof. Leena Ahmad Alfarani 6. The extent to which the Islamic studies curricula content has been achieved for the primary stage (higher grades) of the integrative curriculum principles from the teachers of Islamic studies point of view Mr. Ali Mohamed Ahmed Al-Mahabi 7. The Extent to Which Social Validity Criteria are Met in the Individual Educational Plans of Students with Autism Spectrum Disorder in the City of Jeddah Mrs. Bashaer Meshal Alharty, Co- Prof. Hassan Osama Maajeeny